Effectiveness of an Educational Program on Collegians’ Perception of Healthy Dietary Patterns - Mustafa, Ayed A.; Abdel Wahed, Hala S. (Iraqi National Journal of Nursing Specialties, 2024)
Objective(s): To determine the effectiveness of the educational program on university collegians’ perceptions of healthy dietary patterns, and to determine the relationship between these perceptions and students’ socio-demographic characteristics such as age, sex, marital status, monthly family income, place of residence, and level of education.Methods: A quasi-experimental investigation was performed on students in the University of Mosul to assess the dietary pattern from November 9th of 2022 up to January 2nd of 2023. Non-probability sampling for a sample of (60) students divided into two groups, (study and control groups). Determine the validity of the questionnaire content by presenting it to the experts and using the half-division technique and calculating the Pearson correlation coefficient to determine its validity. A questionnaire has been constructed through extensive review of related literatures to accomplish the study's aims and objectives.Results: The results of data showed that all (60) students in the study sample did not have an adequate level of perception of healthy dietary pattern in pre-test, 12.53 (±3.72). while the results of the post-test after implementing the program results showed that there is an improvement in their perceptions of the healthy dietary pattern in the study group only, 19.43 (±3.98).Conclusion: The study showed that there was an improvement in perceptions of a healthy lifestyle related to dietary pattern in study group compared to those in the control group.Recommendations: The study recommended the need to develop educational programs, lectures, courses and seminars on the benefits of a healthy dietary pattern that university students must follow to increase their perceptions that lead to changing their lifestyle and getting rid of wrong behaviors and habits.